A legal analysis on the effectiveness of enforcement of trade Description Act 2011 in relation to open trade of counterfeit products / Nik Munirah Nik Fuad, Noraisyah Sakinah Mohamed Ismail and Norhazirah Mustaffa Kamal - Nik Fuad, Nik Munirah; Mohamed Ismail, Noraisyah Sakinah; Mustaffa Kamal, Norhazirah (2012)
Trade of counterfeit products in Malaysia is practiced openly. This is proven by existence of Petaling Street, Batu Feringgi Night market, Uptowns and night markets all over this country. In those places, counterfeit products are openly exhibited for sale. This research aimed to analyze the effectiveness of enforcement of Trade Description Act 2011 in relation to open trade of counterfeit products in Malaysia by identifying the problems relating to the enforcement of law and recommend relevant suggestions to improve the current methods of enforcement. Firstly, this paper discussed the meaning of trademark and its application of law in Malaysia. Then, we discussed the provisions of law of criminal prosecution under Trade Description Act 2011. To frame the issues of enforcement, this paper discussed 1) The role of Ministry of Domestic Trade, Co-Operatives and Consumerism (MDTCC) and 2) The Border Measures enforcement under Trade Marks (Amendment) Act 2000 Part XIVA (Section 70C to70P) which the power to enforce was conferred to Royal Malaysian Customs. Interviews with officers from Royal Malaysian Customs and Ministry of Domestic Trade, Co-operatives and Consumerism have become main sources as to identify the problems with enforcement to combat trade of counterfeit products. Interview with a seller or counterfeiter is conducted to give better understanding of how counterfeiting business is being operated in this country. The identifications and analysis of problems faced by enforcement bodies will help the efforts to improve current enforcement of Trade Description Act 2011.